Bis(Nitroxymethylisoxazolyl) Furoxan: A Promising Standalone Melt‐Castable Explosive. Issue 1 (21st January 2020) - Johnson, Eric C.; Sabatini, Jesse J.; Chavez, David E.; Wells, Lucille A.; Banning, Joseph E.; Sausa, Rosario C.; Byrd, Edward F. C.; Orlicki, Joshua A.
Abstract: The synthesis and crystal structure of the heterocyclic explosive bis(nitroxymethylisoxazolyl) furoxan, C10 H6 N6 O10, are described. In addition, we report its physical properties and theoretical performance. This material was found to exhibit standalone melt‐castable explosive properties, with a melting point of 89.8 °C and an onset decomposition temperature of 193.8 °C. Bis(nitroxymethylisoxazolyl) furoxan features an insensitive behavior to impact, friction, and electrostatic discharge, with a calculated detonation pressure about 25 % higher than the state‐of‐the‐art melt‐castable explosive TNT. Abstract : More potential than TNT ? The synthesis, characterization and x‐ray crystal structure of bis(nitroxymethylisoxazolyl) furoxan is described. This energetic material was made on a 25 g scale in a five‐step process in 23 % overall yield and was determined to exhibit standalone melt‐castable explosive properties. This material was found to possess a theoretical detonation pressure of 25.1 GPa, 25 % higher than TNT, while exhibiting good sensitivity values to impact, friction and electrostatic discharge.